Charity marketing : contemporary issues, research and practice - Hyde, Fran, 1969-; Mitchell, Sarah-Louise, 1966- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Charities operate within an increasingly challenging environment, with competition for public engagement, funding and volunteers intensifying. High-profile scandals have knocked public trust and led to changes in regulation and governance. However, the recent COVID-19 pandemic has illustrated how great the need is for charities to provide support in times of need and fill the gap left by inadequate public sector provision. Understanding, and making sense of, this turbulent landscape is vital for charities to survive. This book brings together leading scholars to rigorously explore the contemporary issues facing charity marketing, to challenge students and researchers to think about charity marketing in a way that is creative and impactful. Across thirteen chapters it presents different perspectives and theoretical lenses to stimulate debate and inspire future research, building upon existing nonprofit management textbooks and offering academic rigour to complement the raft of practitioner 'How to' guides. The approach of the book contributes to the growing phenomenon of Theory + Practice in Marketing (TPM). Despite the recent theoretical development of 'strategy-as-practice' construct and special journal editions focusing on TPM, the charity sector has been largely absent from the debate, which is an oversight given the importance of the sector to the jobs, economy and social fabric of our country. This book provides a bridge between the practice of contemporary non-profit organisations, charity marketing and recent academic insight into the challenges, culture and communication and exemplar case studies of nonprofit and charity brands. This edited volume will be of direct interest to scholars and researchers studying charities, public & nonprofit management, and marketing"--
OCLC-licensed vendor bibliographic record.
Keywords: Charities -- Management; Charities -- Marketing; Nonprofit organizations -- Management; Nonprofit organizations -- Marketing; BUSINESS & ECONOMICS / Marketing / Multilevel; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities